KOMPETENSI LULUSAN PENDIDIKAN DASAR DAN PERMASALAHAN - Rizki Ananda; Ayu Supia, Yuyun; Trisya Anjani; Mei Dinda Anggiani; Wardana Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the competencies of primary education graduates and the challenges encountered in achieving them. Graduate competency serves as a critical indicator of the success of the primary education system. However, issues such as low teaching quality, inadequate learning facilities, and unequal access to education remain prevalent. This study adopts a qualitative approach through literature review to identify the factors influencing graduate competency. The findings indicate that improving graduate competency requires a relevant curriculum, enhanced teacher quality, and equitable distribution of educational resources.